Motivation no Jutsu: Exploring the Power of Badge Aesthetics in Gamified Learning - Rodrigues, Luiz; Toda, Armando M.; Palomino, Paula T.; Klock, Ana C. T.; Avila-Santos, Anderson (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
Gamification researchers have discussed the relevance of connecting game elements’ visual appearance to students’ feelings as a way to enhance learning outcomes. However, there is limited evidence from experimental studies on how gamification affects learning experiences. This study tackles this gap by investigating how students’ feelings toward the visual appearance of badges affect their learning experiences in a gamified educational system. We conducted an experimental study (n = 19) comparing non-thematic badges to thematic ones featuring characters from a popular animation brand (i.e., Naruto), while controlling for the moderating effect of students’ enthusiasm towards such brand. The results suggested that connecting gamification designs to students’ feelings through visually appealing game elements can enhance their learning experiences, possibly because most students enjoy the anime and do not like non-thematic badges. Nevertheless, the results also raised concerns about the brand badges, such as distracting students. Thus, this paper informs practitioners and researchers on the value of designing gamification so that its aesthetics connect to students’ feelings and raises concerns on potential issues to be considered and further explored.